Description

Theorem 7.1. Let L K be a finite extension. Then a)[l : K] [L : K] s b) the extension L K is separable iff [L : K] = [L : K] s. Proof. Let M be a normal closure of L : K. Consider first the case when L

Information

Category:
## Resumes & CVs

Publish on:

Views: 32 | Pages: 6

Extension: PDF | Download: 0

Share

Transcript

Theorem 7.1. Let L K be a finite extension. Then a)[l : K] [L : K] s b) the extension L K is separable iff [L : K] = [L : K] s. Proof. Let M be a normal closure of L : K. Consider first the case when L K is an elementary extension. In this case there exists α L such that L = K(α). We know that deg(p(t)) = [L : K] and it follows from Lemma 3.3 that the separable degree [L : K] s is equal to the number of roots of the polynomial p(t) := Irr(α, K, t) in M. Since the number of roots of the polynomial p(t) in M is not bigger then it s degree we see that [L : K] s deg(p(t)) = [L : K]. Moreover [L : K] = [L : K] s iff the polynomial p(t) is separable. So the Theorem 7.1 is true for elementary extensions. Now we prove the Theorem 7.1 by induction in [L : K]. If [L : K] = 1 then L = K and there is nothing to prove. So assume [L : K] 1, choose α L K and write p(t) := Irr(α, K, t). Since [L : K(α)] [L : K] we know from the inductive assumption that [L : K(α)] s [L : K(α)]. It follows now from Lemma 6.5 that [L : K] s = [L : K(α)] s [K(α) : K] s [L : K(α)][K(α) : K] This prove the part a). Assume now that [L : K] = [L : K] s. We want to show that the extension L K is separable. In other words we want to show that for any α L the extension K(α) : K is separable. But we know that [L : K(α)] [L : K(α)] s and [K(α) : K] s [K(α) : K]. Therefore the equality [L : K] = [L : K] s implies the equality [K(α) : K] = [K(α) : K] s and it follows from the beginning of the proof of Theorem 5.2 that the polynomial p(t) := Irr(α, K, t) is is separable. Assume now that the extension L K is separable. We want to show that [L : K] = [L : K] s. We start with the following result. Lemma 7.1. Let K F L be finite extensions. If the extension L : K is separable then the extensions L : F and F : K are also separable. Proof. Suppose the extension L : K is separable. It follows immediately from the definition that the extension F : K is also separable. So it is sufficient to show that the extensions L : F is separable. To show that the extension L : F is separable we have to show that for any α L the polynomial r(t) := Irr(α, F, t) F [t] has simple roots in M. Let 1 2 R(t) := Irr(α, K, t) K[t] Since L : K is separable we know that the polynomial R(t) has simple roots in M. On the other hand r(t) R(t). So all the roots of r(t) are simple. Now we can finish the proof of Theorem 7.1. Let L K be a separable extension. We want to show that [L : K] = [L : K] s. Since [L : K] s = [L : K(α)] s [K(α) : K] s and the field extensions L : K(α) and K(α) : K are separable the equality follows from the inductive assumption. Lemma 7.2. a). Let K F L be finite extensions. If the extensions L : F and F : K are separable then the extension L : K is also separable. b) If K L is a finite separable extension then the normal closure M of L : K is separable over K. The proof of Lemma 7.2 is assigned as a homework problem. Definition 7.1. Let L K be a finite normal field extension, G := Gal(L/K) be the Galois group of L : K. To any intermediate field F, K F L we can assign a subgroup H(F ) Gal(L/K) define by H(F ) := {h Gal(L/K) h(f) = f, f F } By the definition H(F ) = Gal(L : F ). Conversely to any subgroup H Gal(L/K) we can assign an intermediate field extension L H, K L H L where L H := {l L h(l) = l, h H} In other words if A(L, K) is the set of fields F in between K and L and B(L, K) is the set of subgroups of G we constructed maps τ : A(L, K) B(L, K), F H(F ) and η : B(L, K) A(L, K), τ : H L H. The Main theorem of the Galois theory. Let L K a finite normal separable field extension. Then a) Gal(L/K) = [L : K], b) L G = K c) τ η = Id A(L,K) d) η τ = Id B(L,K). Proof. The part a) follows from Theorem 7.1. Proof of b). Let F := L H. As follows from a), the product formula and Theorem 5.1 we have [F : K] = [L : K]/[L : F ] = 1. So F = K. Proof of c). Let F A(L, K) be subfield of L containing K, H(F ) := η(f ) G. Since the extension L K is normal it follows from Lemma 6.1. c) that the extension L F is also normal. So it follows from a) that H(F ) = [L : F ]. Since H(F ) = Gal(L : F ) it follows from b) that L H = F. So τ η(f ) = F. Proof of d) Let U B(L, K) be a subgroup of G and F := L U. Define H := H(F ). We want to show that U = H. By the definition, for any u U, α F we have u(α) = α. In other words U H. As follows from Theorem 5.1 we have [L : F ] = U. On the other hand, it follows from c) that [L : F ] = H. So U = H and the inclusion U H implies that U = H. Lemma 7.3. For a finite field extension L K the following three conditions are equivalent a) L : K is normal, b) for every extension M of K containing L and every K-homomorphism f : L M we have Im(f) L and f induces an automorphism of L c) there exists a normal extension N of K containing L such that for every K-homomorphism f : L N we have Im(f) L,. Proof. We show that a) b) c) a). a) b).we first show that for any α L we have f(α) L. Let p(t) = Irr(α, K, t) K[t] be the irreducible polynomial monic which has a root α L. Since L is normal the polynomial splits in L[t] to a product of linear factors. So all it roots belong to L. Since f : L M is K-homomorphism we know that f(α) M is a root of p(t). So f(α) L. To show that f induces an automorphism of L we observe that dim KL . Since f is an imbedding it induces an automorphism of L. b) c). Follows from Lemma 5.1. c) a). Let p(t) = Irr(α, K, t) K[t] be the irreducible polynomial monic which has a root α L. We want to show that all his roots in a normal closure N of L : K are actually in L. Let β N be a root of p(t). As follows from Lemma 6.1 a) there exists an automorphism f of N such that f(α) = β. Since by c) we have f(l) L we see that β L. lemma 7.4. a) Let L K be a finite extension, F, E L subfields containing K and EF L be the minimal subfield of L containing 3 4 both E and F. If both extensions E : K and F : K are separable then the extension EF : K is separable, b) L s := {α L the extension K(α) : K is separable}. Then L s L is a subfield, c) [L s : K] = [L : K] s I ll leave the proof of lemma 7.4 as a homework. Definition 7.2 Let L K be a finite extension of characteristic p 0. We say that an element α L is purely inseparable over K if there exists n 0 such that α pn K. Lemma 7.5. Let L K be a finite extension and p :=ch (K) 0. The following four conditions are equivalent: P1. L s = K, P2. every element α L is purely inseparable, P3. for every element α L we have Irr(α, K, t) = t pn a for some n 0, a K, P4. there exists a set of generators α 1,..., α m L of L over K [ that is L = K(α 1,..., α m )] such that all elements α i, 1 i m are purely inseparable over K. P1 implies P2. Let M be a normal closure of L over K. Assume P1. Fix α L. We want to show that every element α L is purely inseparable. As follows from Lemma 5.3 we have [K(α) : K] s = 1. Let p(t) := Irr(α, K, t). As follows from Lemma 3.3 to the number of distinct roots of p(t) in M is equal to [K(α) : K] s. So p(t) = (t α) m. I claim that there exists n 0 such that m = p n. Really write m = p n r where r is prime to p. Then we have p(t) = ((t α) pn ) r = (t pn α pn ) r = t pnr rα pn t pn (r 1)r +... where... stay for lower terms. Since p(t) K[t] we see that rα pn K. Since r is prime to p we can divide by r. Therefore α pn K and p(t) = (t α) pn. Since p(t) K[t] we see that α pn K. I ll leave for you to show that P2 implies P3 and that P3 implies P4. P4 implies P1. We have to show that any K-homomorphism f : L M is equal to the identity. Since L = K(α 1,..., α m ) it is sufficient to show that f(α i ) = α i, 1 i m. Since the elements α i are purely inseparable for any i, 1 i n there exists n 0 such that α i is a root of the polynomial p(t) = t pn a. But then p(t) = (t α i ) pn and therefore α i is it s only root. Since f(α i ) is also a root of p(t) we see that f(α i ) = α i. Definition 7.2. Let L K be a finite extension. a) We say that the extension L K is purely inseparable if it satisfies the conditions of Lemma 7.6, b) we define [L : K] i := [L : L s ] = [L : K]/[L : K] s. Now we finish the proof of Theorem 2.1. Remind the Definition 2.3. We say that a finite extension L K satisfies the condition if there exists only a finite number of subfields F L containing K. Theorem 7.2. a) A finite extension L K is elementary iff it satisfies the condition, b) any finite separable extension L K is elementary. Proof of a) We have to show that i) if L K is a finite extension of K which satisfies the condition then the extension L K is elementary and ii) if L K is an elementary extension then it satisfies the condition. The part i) was proven in the second lecture. Now we will proof the part ii). So assume that L = K(α). We want to show that the set A of intermediate fields F, K F L is finite. Let M L be a splitting field of p(t) := Irr(α, K, t) K[t]. Then s p(t) = (t α i ) m i, α i M, m i 0 i=1 Let B be the set of monic polynomials in r(t) M[t] which divide p(t). Since any such monic polynomials in r(t) M[t] has a form s r(t) = (t α i ) n i, α i M, 0 n i m i 0 i=1 we see that the set B is finite. So for a proof of ii) it is sufficient to construct an imbedding of the set A into the set B. Given an intermediate field F, K F L consider the polynomial r F (t) := Irr(α, F, t) F [t]. As we know degr F (t) = [F (α) : F ]. Since F (α) K(α) = L we see that F (α) = L and deg(r F (t)) = [L : F ]. Since p(α) = 0, the polynomial r F (t) F [t] is irreducible in F [t] and r F (α) = 0 we see that r F (t) p(t). So r F (t) B and we constructed a 5 6 map A B. To finish the proof of ii) it is sufficient to show that we can reconstruct the field F if we know the polynomial r F (t). Let F 0 L be the field generated over K by the coefficients of the polynomial r F (t). I claim that F = F 0. By the construction we have r F (t) F 0 [t]. The inclusion r F (t) F [t] implies that F 0 F. Since the polynomial r F (t) F [t] is irreducible it is also irreducible in F 0 [t]. So we see that degr F (t) = [L : F 0 ]. Now the inclusion F 0 F implies that F 0 = F. By the definition the field F 0 is is determined by the knowledge of the polynomial r F (t). To prove b) we have to show that any finite separable extension L K satisfies the condition. In the case when K is a finite field there is nothing to prove. So we assume that the field K is infinite. Since the extension L K is finite we can find α 1,..., α n L such that that L = K(α 1,..., α n ). We have to show that there exists β L such that L = K(β). I ll prove the result for n = 2. The general case follows easily by induction. [ We have run through analogous reduction to the case n = 2 a number of times]. So assume that L = K(α 1, α 2 ). Let M be a normal closure of L, d := [L : K]. Since the extension L K is separable it follows from Theorem 5.2 that there exists d distinct field homomorphisms f i : L M, 1 i d. Consider the polynomial q(t) := (f i (α 1 ) + tf i (α 2 ) f j (α 1 ) tf j (α 2 )) 1 i j d By the construction f i f j for i j. So q(t) 0 and the polynomial q(t) has only finite number of roots. Since K = there exists c K such that q(c) 0. In other words f i (α 1 ) + tf i (α 2 ) f j (α 1 ) + tf j (α 2 ) if 1 i j d. Let β := α 1 + cα 2 for 1 i j d, L := K(β). We want to show that L = L. Let Let g i : L M, i d be the restrictions of f i to L L. Since f i (α) f j (α) for 1 i j d we see that the field homomorphisms g i : L M are distinct. Therefore [L : K] s d = [L : K]. It follows now from Theorem 5.2 that [L : K] [L : K]. Since L L this is possible only if L = L.

Related Search

Similar documents

We Need Your Support

Thank you for visiting our website and your interest in our free products and services. We are nonprofit website to share and download documents. To the running of this website, we need your help to support us.

Thanks to everyone for your continued support.

No, Thanks